Efektivitas Penggunaan Aplikasi Digital untuk Meningkatkan Motivasi Belajar Siswa pada Mata Pelajaran PAI dan Budi Pekerti di SD Islam Teratai Putih Global Bekasi - Fatimah Azzahra Hanifah Heriady; Ayi Sobarna (UNISBA Press, 2022)
Abstract. The purpose of this research was to determine the effectiveness of the use of digital applications to increase student motivation in Islamic education subjects at Elementary School. This study used an empirical quantitative by using a scientific approach or called a quantitative approach with an experimental method. Several data collection techniques used were pretest-posttest, interview, and study documentation. This quantitative research is presented in the form of descriptive statistics which clearly describe how the differences in the level of student learning motivation in Islamic Studies subjects before and after being given treatment. The results of this study can be seen changes in the level of students' learning motivation at Islamic education subjects, including: (a) the pretest result of experimental class shows that the level of student learning motivation is in the medium category with an average score (mean) of 83.00, then the posttest results showed a change in the level of student motivation to the high category with an average value (mean) of 111.50. (b) the pretest result of control class showed that the level of student learning motivation was in the medium category with an average score (mean) of 84.13, then the posttest results showed an increase in the average score (mean) of 88.63 but the level of student motivation was still in the medium category. (c) the implementation of Islamic education learning by using digital applications was carried out well, each digital application has a different function but related to each other such as WhatsApp as a communication liaison between educators and students and video conference as a distance learning media. Abstrak. Tujuan dari penelitian ini adalah untuk mengetahui efektivitas penggunaan aplikasi digital untuk meningkatkan motivasi belajar siswa pada mata pelajaran pendidikan agama Islam di Sekolah Dasar. Penelitian ini menggunakan kuantitatif empiris dengan menggunakan pendekatan saintifik atau disebut pendekatan kuantitatif dengan metode eksperimen. Beberapa teknik pengumpulan data yang digunakan adalah pretest-posttest, wawancara, dan studi dokumentasi. Penelitian kuantitatif ini disajikan dalam bentuk statistik deskriptif yang secara gamblang menggambarkan bagaimana perbedaan tingkat motivasi belajar siswa pada mata pelajaran IPS sebelum dan sesudah diberikan perlakuan. Hasil penelitian ini dapat dilihat perubahan tingkat motivasi belajar siswa pada mata pelajaran PAI, antara lain: (a) hasil pretest kelas eksperimen menunjukkan bahwa tingkat motivasi belajar siswa berada pada kategori sedang dengan skor rata-rata. (mean) sebesar 83,00, maka hasil posttest menunjukkan adanya perubahan tingkat motivasi belajar siswa ke kategori tinggi dengan nilai rata-rata (mean) sebesar 111,50. (b) hasil pretest kelas kontrol menunjukkan bahwa tingkat motivasi belajar siswa berada pada kategori sedang dengan skor rata-rata (mean) sebesar 84,13, kemudian hasil posttest menunjukkan peningkatan skor rata-rata (mean) sebesar 88,63 tetapi tingkat motivasi siswa masih dalam kategori sedang. (c) pelaksanaan pembelajaran pendidikan agama Islam dengan menggunakan aplikasi digital terlaksana dengan baik, masing-masing aplikasi digital memiliki fungsi yang berbeda namun saling berkaitan satu sama lain seperti WhatsApp sebagai penghubung komunikasi antara pendidik dan peserta didik dan video conference sebagai media pembelajaran jarak jauh.